Experimental study of a domestic refrigerator with POE-Al2O3 nanolubricant - Mohd Yusof, Taib; Azim, Arshad; Suziyana, Mat Dahan; Lee, Giok Chui; Firdaus, Basrawi
This paper presents the performance of a minibar domestic refrigerator operating with and without nanoparticles of alumina oxide, Al2O3. The Al2O3 nanoparticles were mixed with polyolester (POE) lubricant to form nano-lubricant at 0.2% concentration by volume and were prepared via a two-step method. The nano-lubricant was introduced into the refrigerator at different refrigerant charges ranging from 36 to 44 psi. The evaluation was carried out by determining the general performance in terms of refrigeration capacity (QL), compressor work, coefficient of performance (COP), and the power and energy consumption of the system working with both lubricants, POE-Al2O3 and POE. The refrigerator attained its optimum operating level at 42 psi for both. It also worked normally and safely with POE-Al2O3 lubricant during the experiment. The performance of the refrigerator operating with POE-Al2O3 was improved compared with the system working with POE in terms of energy consumption and COP. The energy consumption of the refrigeration system with POE-Al2O3 at optimum refrigerant charge was the minimum and maximum COP of 321 Wh and 2.67. The highest percentage of energy consumption reduction was 2.1% at the optimum refrigerant charge. Thus, the addition of Al2O3 nanoparticles to the base fluid (POE) gave better performance and reduction of power consumption.